ENDOVASCULAR OCCLUSION OF THE PATENT FORAMEN OVALE AS PART OF ANTIARRHYTHMIC TREATMENT OF A PATIENT WITH PERSISTENT ATRIAL FIBRILLATION (CASE REPORT) - Zhelyakov, E. G.; Tereshchenko, A.S.; Merkulov, E.V.; Ardashev, A.V. (Interdisciplinary Approaches to Medicine, 2023)
Below is a case report of treatment of a patient with persistent tachysystolic atrial fibrillation (AF), chronic heart failure (CHF) with a moderately reduced left ventricular ejection fraction (EF) and patent foramen ovale (PFO) with an atrial septal aneurysm. A 58-year-old man (with body mass index of 27.8 kg/m2) with tachysystolic persistent AF (duration 3 months) was hospitalized due to an increase in CHF symptoms (CHF functional class according to NYHA is II-III). The patient had been constantly receiving therapy in accordance with current recommendations (angiotensin receptor blockers, diuretics, beta-blockers, amiodorone and rivaroxaban). Transthoracic echocardiography showed a moderate decrease in ejection fraction (EF) (41%), an increase in the left (47 mm) and right (51x74 mm) atria. The patient underwent AF radiofrequency catheter ablation (RFA) in the left atrium, which identified PFO. The final stage of RFA was performed by external electrical cardioversion with successful restoration of sinus rhythm. Four months after RFA, despite a stable sinus rhythm, the patient maintained a moderately reduced LV EF (44%) and dilatation of the left (44 mm) and right (43x65 mm) atria. Transesophageal echocardiography revealed an aneurysmally altered atrial septum and a positive bubble test with a large number of bubbles. In accordance with current recommendations, the patient had indications for primary prevention of stroke - endovascular occlusion of the PFO, which was performed. Three months after PFO closure, the patient discontinued diuretics, amiodarone, and rivaroxaban. Combined therapy in a patient with persistent AF, with a moderately reduced EF and verified PFO, which included pathogenetic therapy for CHF, prescription of antiarrhythmic drugs, RFA of the AF substrate, and interventional closure of the PFO, made it possible to effectively control sinus rhythm, significantly reduce the manifestations of CHF and provide primary prevention of embolic disorders.